(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Cognitive impairment in patients with chronic heart failure remains one of the most pressing problems in neurology, and the urgency of the problem is determined by the frequency of complications resulting from this pathology and the lack of adequate effective treatment.